Mom the Chemistry Professor Personal Accounts and Advice from Chemistry Professors who are Mothers (Springer International Publishing, 2018)
When is the "right" time? How can I meet the demands of a professorship whilst caring for a young family? Choosing to become a mother has a profound effect on the career path of women holding academic positions, especially in the physical sciences. Yet many women successfully manage to do both. In this second edition, which is a project of the Women Chemists Committee (WCC) of the American Chemical Society (ACS), 40 inspirational personal accounts describe the challenges and rewards of combining motherhood with an academic career in chemistry. The authors are all women at different stages of their career and from a range of institution types, in both tenure and non-tenure track positions. The authors include women from different racial and ethnic backgrounds, who became mothers at different stages of their career, and who have a variety of family structures. Aimed at undergraduate and graduate students of chemistry, as well as postdoctoral fellows and early career faculty, these contributions serve as examples for women considering a career in academia but worry about how this can be balanced with other important aspects of life. The authors describe how they overcame particular challenges, but also highlight aspects of the system, which could be improved to accommodate women academics, and particularly encourage more women to take on academic positions in the sciences.